AN ANALYSIS OF POLITENESS STRATEGIES USED BY DEDDY CORBUZIER IN HITAM PUTIH TALK SHOW - Mega Selfia; Leni Marlina (Universitas Negeri Padang, 2016)
Politeness strategies (strategi kesantunan) are ways that used by someone to convey her/his utterances politely. Politeness strategies can be observed in daily life and in talk shows. One of the most famous popular talk shows among Indonesia’s viewer is Hitam Putih talk show. This paper aims to describe the types of politeness strategies and dominant politeness strategies used by Deddy Corbuzier in interviewing especially in asking guest stars. Theory that used to describe an analysis of politeness strategies is Brown and Levinson theory (1987). There are four politeness strategies that are classified by Brown and Levinson, they are Bald on Record, Positive Politeness, Negative Politeness and Off Record. This result finding shows that the host of Hitam Putih talk show used four types of politeness strategies with different presentations. The most dominant politeness srategy used was Positive Politeness with 58 %. Another dominant politeness strategy used was Bald on Record (18 %), Negative Politeness (15 %) dan Off Record (9 %). It can be concluded that positive politeness strategy (strategi kesantunan positif) is the most dominant strategy used by the host in Hitam Putih talk show.